Computational number theory - Das, Abhijit (Discrete mathematics and its applications, 2013)
"Preface This book is a result of my teaching a Masters-level course with the same name for five years in the Indian Institute of Technology Kharagpur. The course was attended mostly by MTech and final-year BTech students from the department of Computer Science and Engineering. Students from the department of Mathematics and other engineering departments (mostly Electronics and Electrical Engineering, and Information Technology) also attended the course. Some research students enrolled in the MS and PhD programs constituted the third section of the student population. Historically, therefore, the material presented in this book is tuned to cater to the need and taste of engineering students in advanced undergraduate and beginning graduate levels. However, several topics that could not be covered in a one-semester course have also been included in order to make this book a comprehensive and complete treatment of number-theoretic algorithms. A justification is perhaps due to the effect why another textbook on computational number theory was necessary. Some (perhaps not many) textbooks on this subject are already available to international students. These books vary widely with respect to their coverage and technical sophistication. I believe that a textbook specifically targeted towards the engineering population is somewhat missing. This book should be accessible (but is not restricted) to students who have not attended any course on number theory. My teaching experience shows that heavy use of algebra (particularly, advanced topics like commutative algebra or algebraic number theory) often demotivates students"--